Design analysis of polarization-doped N-face InGaN/GaN light-emitting diodes with different AlxGa1−xN graded layers. (January 2015) - Yang, G.F.; Tong, Y.Y.; Xie, F.; Yan, D.W.; Wang, F.X.
Abstract: The polarization-doped N-face blue InGaN/GaN light-emitting diodes (LEDs) with different Al content in the p-type graded Al x Ga1− x N layers are investigated numerically, and the polarization-doped Ga-face LED with the same structure is simultaneously simulated for comparison. The proposed N-face LEDs with low content in the graded Al x Ga1− x N layer exhibit significant improvement for the light output power and hole injection efficiency at high applied voltages compared with the Ga-face counterpart. The enhanced performance for the N-face polarization-doped LEDs is explained by the simulated energy band diagrams, distribution of electric field, carrier concentration and radiative recombination rate in the quantum wells.